ETHNOMATHEMATICS POP-UP BOOK ON GEOMETRY IN TRADITIONAL LAMPUNG HOUSES: Lampung, Indonesia - Pradana, Kenny Candra; Rohani, Anisa; Minadja, Adji W. S. (Jurnal Math-UMB.EDU, 2026)
This study aims to develop an ethnomathematics-based pop-up book as a learning medium, integrating geometric concepts within the context of traditional Lampung houses, to enhance students' conceptual understanding of mathematics and to evaluate the responses of teachers and students as well as the effectiveness of the media. The research employed the Borg & Gall development model with seven steps: data collection, planning, initial draft development, preliminary testing, product revision, main field testing, and dissemination and implementation. Data were analyzed using qualitative and quantitative descriptive methods. Validation results indicated that the media fell into the "highly feasible" category, with a score of 90% from material and media experts. Small-scale testing received a "very interesting" response of 92%, while large-scale testing achieved a 94% positive response from 29 students. Improvement in conceptual understanding was evidenced by an N-Gain score of 0.89 (high category), and the media’s effectiveness was shown by an effect size of 1.06 (effective category). The findings imply that the ethnomathematics-based pop-up book is effective in supporting culturally responsive mathematics learning and can serve as an innovative and contextual alternative learning medium. Keywords: Ethnomathematics; Geometry; Pop-Up Book; Research and Development; Traditional Lampung Houses